94 Percutaneous Mitral Repair in Hypertrophic Cardiomyopathy. (31st May 2014) - Pantazis, Antonis; Hong Cheang, Mun; Mullen, Michael; Elliott, Perry; Mckenna, William; Kumar Aggarwal, Suneil; Teresa TomeEsteban, Maria; Reinthaler, Markus; Delahunty, Nicola
Abstract : Objectives: To describe our Centre's experience of percutaneous mitral repair in Hypertrophic Cardiomyopathy (HCM). Background: Exertional dyspnoea in HCM is multi-factorial. Mitral regurgitation (MR) frequently co-exists with or occurs as a result of HCM related haemodynamic abnormalities like left ventricular outflow tract obstruction (LVOTO) and systolic anterior motion of the mitral valve (SAM). Significant MR in HCM can be a major contributor to symptoms. Current interventional treatments which include alcohol septal ablation, surgical myectomy and mitral valve replacement are not always suitable and may be associated with increased risk. Surgical mitral repair using the Alfieri stitch can be successful in reducing MR due to SAM and can improve LVOTO. However, the application of percutaneous mitral repair using MitraClip system (which mimics the Alfieri stitch) in HCM has not been previously documented. We describe our experience of treating six HCM patients with this technique. Methods: Percutaneous mitral repair using the MitraClip System (Evalve, Inc., Menlo Park, CA, USA) technology was performed on six HCM patients between 2010–2012. All cases were discussed in a multi-disciplinary team setting beforehand. Patients who were not suitable for conventional treatment were offered this procedure if deemed clinically appropriate. All patients were subsequently followed-up for 12 months. Improvement in exercise capacity was assessed by a combination of clinical history and 6 min walk test. The echocardiographic images and case notes were retrospectively reviewed. Results: MitraClip implants were completed successfully without any significant peri-procedure complications in all patients. Our experience suggests that it is associated with low procedural risk and relatively short inpatient stay (average of 4 days including pre-procedure admission the day before procedure). Below is a summary of our outcomes. Conclusion: Percutaneous mitral repair using MitraClip is feasible and may be performed safely in HCM. This technique can be effective in reducing mitral regurgitation and improving symptoms in HCM. However, MR recurrence was an observed complication in our cohort. Percutaneous mitral repair using the MitraClip technology may have a future role to play in the symptomatic management of HCM. More studies are needed to understand how MitraClip alters haemodynamics in HCM and how that may contribute to symptom improvement.